Effects of Differently Located Clearance on the Dynamic Responses of a Two-Degree-of-Freedom Vibration System - Yan Yang; Guanwei Luo (Shock and Vibration)
The mechanical model of a two-degree-of-freedom forced harmonic vibration system with multiclearance rigid constraints is established, considering the location schemes of symmetrical both-sided clearance and asymmetrical multiple clearance. Existence domains, correlative distributions, and bifurcation scenarios of periodic vibrations are analyzed using multiparameter and multiperformance cosimulation. Pattern diversity, distribution, and occurrence mechanism of the subharmonic impact motion sequences in the tongue-shaped transition regions among the neighboring fundamental periodic motions of the vibration systems are investigated. The emergent behavior of sticking process of fundamental periodic vibration, the occurrence law of chattering-impact motion, and the interaction of different modes of sticking are discussed. According to the sampling ranges of parameters, three multiple heterogeneous constraint conditions are explored; the effects of differently clearance location and values on the dynamic responses and the transition region of fundamental periodic vibrations and subharmonic motions are particularly analyzed. Hence, the reasonable clearance arrangement scheme and numerical optimization combination are determined and the ideal parameter domain of the vibration system is obtained.